Genotypic, Phenotypic Identification and Antibiogram Assay of Mrsa Isolated from Healthy Individuals in Wasit Province - Haneen Saad Farhan1 , Zainab N. Al-Saadi2 , Jassim Fatehi Ali3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Staphylococcus aureus is a Gram-positive, facultative anaerobic, non-spore-forming, coagulase -positivebacterium. the Methicillin resistance is mostly mediated by the presence of mecA gene acquisition of mecAgene leads to altered penicillin binding protein (PBP), called PBP2a, with low binding affinity to methicillin.A total of 52 S. aureus strains were analysed. Antibiogram assay for 52 healthy carriers of MRSA isolates byusing Vitek 2 system to examine 16 different antibiotics.Methicillin resistance was confirmed by presenceof the mecA gene by PCR. Of 52 S. aureus samples, 52 isolates of them were MRSA confirmed by targetingmecA gene using PCR. Aims of this study detect methicillin resistant Staphylococcus aureus from nose ofhealthy individuals in Wasit province and confirming that by PCR to detect mecA Gene.